2018
DOI: 10.33314/jnhrc.v16i2.1570
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic Index of Plasma in Postmenopausal Women

Abstract: Background: Hyperlipidemia is one of the important risk factor for development of cardiovascular disease in post menopausal women.Our study compared the serum lipid profile and atherogenic index of plasma between premenopausal and post menopausal women.Methods: This was a cross sectional study conducted in Kathmandu Medical College. A total number of 194 women in the age group 30 to 60 years were studied. They include 108 postmenopausal women and 86 premenopausal controls. Total cholesterol, low density lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…CVD is known to have gender differences in presentation, prevalence, and clinical outcomes [53][54][55]. For instance, men and postmenopausal women showed an increased risk of IHD compared to premenopausal women [56]. It is thought that postmenopausal women have atherogenic LDL profiles comparable to those in men because of aging and the event of menopause [57].…”
Section: Discussionmentioning
confidence: 99%
“…CVD is known to have gender differences in presentation, prevalence, and clinical outcomes [53][54][55]. For instance, men and postmenopausal women showed an increased risk of IHD compared to premenopausal women [56]. It is thought that postmenopausal women have atherogenic LDL profiles comparable to those in men because of aging and the event of menopause [57].…”
Section: Discussionmentioning
confidence: 99%
“…AIP was calculated as the logarithmical transformed ratio of molar concentrations of TG to HDL-C [ 25 ]. AIP was classified as follows: low CVD risk <0.1, medium risk 0.1–0.24, and high risk >0.24 [ 17 ].…”
Section: Data Collectionmentioning
confidence: 99%
“…A high AIP has been used as a standalone index for estimating cardiac risk [ 15 ]. In addition, AIP was a strong predictor of atherosclerosis and myocardial infarction [ 16 , 17 ]. Previous studies revealed that postmenopausal women were at an increased risk for developing CVD because of the elevated atherogenic lipid profile [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atherogenic index is a strong marker for assessing the risk of atherosclerosis and coronary heart disease in vessels. As the AI increases, the risk of atherogenesis increases [44,45]. Estradiol and the antihyperlipidemic drugs employed in this study signi cantly decreased the AI and CRI.…”
Section: Discussionmentioning
confidence: 64%